The turn-around upside-down alphabet book - Ernst, Lisa Campbell (Simon & Schuster Books for Young Readers, 2004)
An alphabet book in which each letter becomes three different objects as the book is turned different directions, as when A becomes a bird's beak, a drippy ice cream cone, and the point of a star.